WWF and Arctic Environmental Cooperation in the 1990s : A Case Study of a NGO in International Cooperation - Salonen, Satu (Helsingfors universitet, 2013)
The focus of the thesis is to analyse through the case study of World Wide Fund for Nature (WWF) how did the environmental NGOs respond to the state level cooperation in the Arctic in the 1990s. Time frame of the thesis ranges from 1989 to 1998; from the preparations for the first state-level meeting on the Arctic environmental cooperation until the establishment of the Arctic Council and accreditation of WWF as permanent observer. The thesis analyses how WWF saw the Arctic cooperation, how the Arctic states reacted to WWF’s aspirations to be included, and how WWF pursued a role in the cooperation. Moreover, the purpose of this thesis is, through examining the case of WWF in the Arctic state-level cooperation, to contribute to the research of NGOs acting and pursuing participation in the state-level cooperation forums. The source material of the thesis can be divided into three categories: archive materials; journals; and declarations, documents and strategies of the Arctic cooperation forums. The main archive materials are from the Archives of the Finnish Ministry for Foreign Affairs, retaining memorandums, reports, correspondence between officials, diplomats and representatives of NGOs, minutes, and documents. The main publication that has been used as a source is the WWF Arctic Program’s publication Arctic Bulletin. In addition, declarations, strategies and various documents from WWF and Arctic cooperation forums have been used to supplement the archive materials and Arctic Bulletin. Through the source materials different views and strategies of WWF have been examined alongside with the views of Arctic states on WWF’s role in the cooperation. The analytical frame has been constructed against non-governmental organizations acting in the state-level cooperation. The analytical frame is also closely connected to the use of soft-law arrangements in international cooperation as one of their justifications is the inclusion of non-state actors, including NGOs. Through combining methodological features of a case ...